Cross-Cultural Adaptation and Validation of the Persian Version of the Oxford Knee Score in Patients with Knee Osteoarthritis - Ebrahimzadeh, Mohammad Hosein (Iran J Med Sci, 2014)
Background: The Oxford Knee Score (OKS) is a short patient-reported outcome instrument that measures pain and physical activity related to knee osteoarthritis. The purpose of this study is to evaluate, construct validity and consistent reliability of the Persian version of the OKS. Methods: The case series consisted of 80 patients who were clinically diagnosed with having knee osteoarthritis. All patients were requested to fill-in the Persian OKS and Short-Form 36 Health Survey (SF-36). Correlation analysis between the Persian versions of these two instruments was then carried out. The scores of the Persian SF-36 were used to evaluate convergent and divergent validity of the 12-item Persian OKS. Results: From a total of 80 patients, 63 were female (79%) and the remaining 17 were male (21%) with a mean age of 52.2 years. In the present study, high Cronbach’s alpha of 0.95 confirms excellent internal consistency of the Persian OKS scale similar to previous investigations. The results confirm that the Persian version of this instrument is valid and reliable, similar to its English index and its subsequent translations in different languages. Conclusion: The Persian OKS is a reliable instrument to evaluate knee function in patients with knee osteoarthritis and is a useful tool for outcome measurement in clinical research.